answersLogoWhite

0

9X - 7 = 6

add 7 to each side

9x - 7 + 7 = 6 + 7

9X = 13

divide both sides integers by 9

(9/9)X = 13/9

X = 13/9

=========check in original equation

9(13/9) - 7 = 6

13 - 7 = 6

6 = 6

--------checks

User Avatar

Wiki User

12y ago

Still curious? Ask our experts.

Chat with our AI personalities

RossRoss
Every question is just a happy little opportunity.
Chat with Ross
RafaRafa
There's no fun in playing it safe. Why not try something a little unhinged?
Chat with Rafa
DevinDevin
I've poured enough drinks to know that people don't always want advice—they just want to talk.
Chat with Devin

Add your answer:

Earn +20 pts
Q: What is 9x - 7 equals 6?
Write your answer...
Submit
Still have questions?
magnify glass
imp